Chemometric discrimination of Hylocereus undulatus from different geographical origins via their metabolic profiling and antidiabetic activity. (15th March 2023) - Younis, Inas Y.; Ibrahim, Rana M.; El-Halawany, Ali.M.; Hegazy, Mohamed-Elamir F.; Efferth, Thomas; Mohsen, Engy
Highlights: Peels and pulps of dragon fruits from different geographical origins were analyzed using LC/HRMS. The antioxidant, advanced glycation end product and alpha-glucosidase inhibition of different samples were compared. Peels were richer in phenolics and secondary metabolites than pulps. Activity of all peels were more potent than pulps. Chemometric analysis were carried out to differentiate between samples from different geographical origins. Abstract: Hylocereus spp. known as dragon fruit is an exotic fruit that belongs to the Cactaceae family. LC-QTOF-MS and multivariate statistical tools were established to analyze differences in the composition of dragon fruit peel and pulp from Egypt, Germany, Philippines, and China. The α-glucosidase inhibitory effects of different extracts were carried out along with the anti-glycation end products (AGE) using BSA-fructose, BSA-methylglyoxal, and arginine-methylglyoxal assays. In addition, the total antioxidant capacity was investigated as a complementary mechanism to AGE formation. Principal component analysis revealed that dragon fruits from China and Egypt were the most distinct among all samples due to betalains content. Orthogonal projection to latent structures-discriminant analysis identified 16 compounds highly correlated to the antiglycation activity such as betanin, γ -aminobutyric acid, neobetanin, and portulacaxanthin II. Pulp extracts were more active than peels as inhibitors of α -glucosidase. While peels were more active as AGE formation inhibitors and as antioxidants.